2016
DOI: 10.1177/1521025116670208
|View full text |Cite
|
Sign up to set email alerts
|

Getting College Students Back on Track

Abstract: The present study examines the outcomes of a 5-week summer bridge writing program at a Midwestern, urban, public university designed to provide remedial instruction for incoming first-year college students, approximately 500 students annually for 7 years. Regression results showed that program participation was a positive, significant predictor on the outcomes of 6-and 4-year graduation, first-year earned credits, and first-year college grade point average, even after controlling for demographic and academic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Quantitative results indicated that students who completed a pre-entry program had an overall higher GPA than their peers who did not complete the program (Hermann et al, 2020;van Herpen et al, 2020). Furthermore, researchers examining longitudinal data found that pre-entry participants experienced academic momentum that, in turn, improved retention and graduation rates (Howard & Sharpe, 2019;Kodama et al, 2018;Wachen et al, 2018). A gap in literature exists, however, in that more research is needed to collect baseline measures of academic self-efficacy and the strategies within these pre-entry programs that affect students' self-efficacy (Pennington et al, 2018).…”
Section: Pre-entry Programsmentioning
confidence: 99%
“…Quantitative results indicated that students who completed a pre-entry program had an overall higher GPA than their peers who did not complete the program (Hermann et al, 2020;van Herpen et al, 2020). Furthermore, researchers examining longitudinal data found that pre-entry participants experienced academic momentum that, in turn, improved retention and graduation rates (Howard & Sharpe, 2019;Kodama et al, 2018;Wachen et al, 2018). A gap in literature exists, however, in that more research is needed to collect baseline measures of academic self-efficacy and the strategies within these pre-entry programs that affect students' self-efficacy (Pennington et al, 2018).…”
Section: Pre-entry Programsmentioning
confidence: 99%
“…While some have developed fresh conceptual perspectives on transitions (see Baker, 2018a;Nordquist, 2017), many rely on rigid and linear understandings. Such approaches view the transition as a process that can be organized in stages (Everitt-Reynolds et al, 2018), a difficult moment to be smoothed over and bridged (Hebdon, 2015;Kodama et al, 2018), and writing in transition as a process of academic acculturation that should lead to academic success and curricular progression (Jessen & Elander, 2009;Regalado, 2004;Stokes, 2014). However, these positionings are often implicit, and only a few studies on academic writing have fully explored the concept of transition.…”
Section: Introductionmentioning
confidence: 99%
“…While some have developed fresh conceptual perspectives on transitions (see Baker, 2018a;Nordquist, 2017), many rely on rigid and linear understandings. Such approaches view the transition as a process that can be organized in stages (Everitt-Reynolds et al, 2018), a difficult moment to be smoothed over and bridged (Hebdon, 2015;Kodama et al, 2018), and writing in transition as a process of academic acculturation that should lead to academic success and curricular progression (Jessen & Elander, 2009;Regalado, 2004;Stokes, 2014). However, these positionings are often implicit, and only a few studies on academic writing have fully explored the concept of transition.…”
Section: Introductionmentioning
confidence: 99%